Bronchom assuages airway hyperresponsiveness in house dust mite-induced mouse model of allergic asthma and moderates goblet cell metaplasia, sub-epithelial fibrosis along with changes in Th2 cytokines and chemokines - Balkrishna, Acharya; Sinha, Sandeep; Karumuri, Shadrakbabu; Maity, Madhulina; Dev, Rishabh; Varshney, Anurag (Frontiers in Immunology, 2024)
Background: Asthma is a common obstructive airway disease with an inflammatory etiology. The main unmet need in the management of asthma is inadequate adherence to pharmacotherapy, leading to a poorly-controlled disease state, necessitating the development of novel therapies. Bronchom is a calcio-herbal formulation, which is purported to treat chronic asthma. The objective of the current study was to examine the in-vivo efficacy of Bronchom in mouse model of allergic asthma. Methods: Ultra high performance liquid chromatography was utilized to analyse the phytocompounds in Bronchom. Further, the in-vivo efficacy of Bronchom was evaluated in House dust mite (HDM)induced allergic asthma in mice. Mice were challenged with aerosolized methacholine to assess airway hyperresponsiveness. Subsequently, inflammatory cell influx was evaluated in bronchoalveolar lavage fluid (BALF) followed by lung histology, wherein airway remodeling features were studied. Simultaneously, the levels of Th2 cytokines and chemokines in the BALF was also evaluated. Additionally, the mRNA expression of pro-inflammatory and Th2 cytokines was also assessed in the lung along with the oxidative stress markers. Results: Phytocompounds present in Bronchom included, gallic acid, protocatechuic acid, methyl gallate, rosmarinic acid, glycyrrhizin, eugenol, 6-gingerol and piperine. Bronchom effectively suppressed HDM-induced airway hyperresponsiveness along with the influx of leukocytes in the BALF. Additionally, Bronchom reduced the infiltration of inflammatory cells in the lung and it also ameliorated goblet cell metaplasia, sub-epithelial fibrosis and increase in α-smooth muscle actin. Bronchom decreased Th2 cytokines (IL-4 and IL-5) and chemokines (Eotaxin and IP-10) in the BALF. Likewise, it could also suppress the mRNA expression of pro-inflammatory cytokines (TNF-α, IFN-, IL-6 and IL-33), and IL-13. Moreover, Bronchom restored the HDM-induced diminution of endogenous anti-oxidants (GSH and SOD) and the increase in pro-oxidants (GSSG and MDA). Furthermore, Bronchom could also decrease the nitrosative stress by lowering the observed increase in nitrite levels. Conclusion: Taken together, the results of the present study data convincingly demonstrate that Bronchom exhibits pharmacological effects in an animal model of allergic asthma. Bronchom mitigated airway hyperresponsiveness, inflammation and airway remodeling evoked by a clinically relevant allergen and accordingly it possesses therapeutic potential for the treatment of asthma.